Criminal Acts of Corruption Article 2 and Article 3 According to Law Number 31 Of 1999 as Amended by Law Number 20 of 2001 Concerning Eradication of Criminal Acts of Corruption (Case Study: Supreme Court Decision No. 260 PK/2011 and Pid.SUS/2011 Supreme Court No. 537 K/Pid.Sus/2014) - Dwi Seno Wijanarko (Budapest International Research and Critics University, 2022)
One of the regulations in the criminal act of corruption is in Article 2 and Article 3 Law Number 31 of 1999 Jo. Law Number 20 of 2001 concerning the Eradication of Corruption Crimes. In this research, there are 2 (two) research problems. First, how many years of the main sentence can be imposed on the defendant Jimmy Rimba Rogi S.Sos in the case of corruption in the Supreme Court's decision no. 260 PK/Pid.Sus/2011? Second, Can the defendant's political rights be revoked as additional punishment? The research method used is the juridical-normative legal research method. The research resulted in 2 (two) conclusions, namely as follows. First, that the concept of restorative justice in convicting perpetrators of criminal acts of corruption does not completely eliminate criminal sanctions, but prioritizes the provision of sanctions that emphasize efforts to recover from crimes. In this case, the author is of the opinion that there are at least 2 (two) concepts of punishment for perpetrators of corruption that can be applied according to a restorative justice approach, namely: first, recovery of state losses in the form of punishment in the form of forced labor for perpetrators of corruption whose proceeds are confiscated for the state and the imposition of social sanctions. . Second, the defendant's political rights can be revoked as an additional penalty. Additional punishment in the form of revocation of certain rights does not mean that the rights of the convict can be revoked altogether. The revocation does not include the revocation of the right to life, civil (civil) rights, and constitutional rights. There are two things regarding the revocation of certain rights, namely: it is not automatic, must be determined by a judge's decision and is not valid for life, there is a certain period of time according to the applicable laws and regulations with a judge's decision. Based on these provisions, the imposition of additional criminal revocation of political rights against the convict is not contrary to the Criminal Code as long as the revocation of rights is concurrent and does not exceed the period of application as has been applied by law.